2012
DOI: 10.1016/j.neuro.2011.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Fetal exposure to propoxur and abnormal child neurodevelopment at 2 years of age

Abstract: Objective Our aim was to determine the effects of fetal exposure to propoxur and pyrethroids, on child neurodevelopment at 2 years of age. Patients and Methods Mothers were prospectively recruited during mid-pregnancy in Bulacan, Philippines where multiple pesticides including propoxur, cyfluthrin, chlorpyrifos, cypermethrin, pretilachlor, bioallethrin, malathion, diazinon and transfluthrin are used. To detect prenatal exposure to these pesticides, maternal hair and blood, infant’s hair, cord blood, and meco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 51 publications
0
42
0
Order By: Relevance
“…While these and other studies found a significant exposure to CAs during development, we found few epidemiological studies describing developmental effects of this class of insecticide, and all of them focused on prenatal exposures (SM Table 6). In the Philippines, Ostrea and collaborators (Ostrea Jr and others 2012) identified a significant relationship between prenatal propoxur exposure and slower motor development for children at 2 years of age. Shelton and collaborators (Shelton and others 2014) used commercial pesticide application data from the California Pesticide Use Report to investigate whether residential proximity to agricultural pesticides during pregnancy was associated with autism spectrum disorders or developmental delay (delayed cognitive or adaptative development).…”
Section: Carbamates (Cas)mentioning
confidence: 99%
“…While these and other studies found a significant exposure to CAs during development, we found few epidemiological studies describing developmental effects of this class of insecticide, and all of them focused on prenatal exposures (SM Table 6). In the Philippines, Ostrea and collaborators (Ostrea Jr and others 2012) identified a significant relationship between prenatal propoxur exposure and slower motor development for children at 2 years of age. Shelton and collaborators (Shelton and others 2014) used commercial pesticide application data from the California Pesticide Use Report to investigate whether residential proximity to agricultural pesticides during pregnancy was associated with autism spectrum disorders or developmental delay (delayed cognitive or adaptative development).…”
Section: Carbamates (Cas)mentioning
confidence: 99%
“…56 Propoxur, 57 a carbamate pesticide, and permethrine, 58 a member of the pyrethroid class of pesticides, have recently been linked to neuro developmental deficits in children.…”
Section: Introductionmentioning
confidence: 99%
“…However, they did find an inverse relationship between mental scores and PBO exposure (1.2 point decrement per log-unit increase in PBO exposure). Ostrea Jr. et al reported no significant effect between exposures to the PYREs bioallethrin, transfluthrin, cyfluthrin and/or cypermethrin and child development at two years of age [16]. However, Xue et al found a negative and significant relationship of prenatal pyrethroid exposure and neural and mental development of Chinese infants at one year of age [17].…”
Section: Introductionmentioning
confidence: 99%